2015
DOI: 10.1007/s00253-015-6893-6
|View full text |Cite
|
Sign up to set email alerts
|

New primers for detecting and quantifying denitrifying anaerobic methane oxidation archaea in different ecological niches

Abstract: The significance of ANME-2d in methane sink in the environment has been overlooked, and there was no any study evaluating the distribution of ANME-2d in the environment. New primers were thus needed to be designed for following research. In this paper, a pair of primers (DP397F and DP569R) was designed to quantify ANME-2d. The specificity and amplification efficiency of this primer pair were acceptable. PCR amplification of another pair of primers (DP142F and DP779R) generated a single, bright targeted band fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…no. FN429785); 4% of sequences (OTU74) formed a cluster with denitrifying anaerobic methane oxidation archaea [19]; the remaining sequences (approximately 2% of all analyzed ANME-2d sequences, OTU101) grouped with sequences of archaea from sediments of Honghu Lake (HM244209).…”
Section: Diversity Of the Anme-2d 16s Rrna Genes In Librariesmentioning
confidence: 99%
See 2 more Smart Citations
“…no. FN429785); 4% of sequences (OTU74) formed a cluster with denitrifying anaerobic methane oxidation archaea [19]; the remaining sequences (approximately 2% of all analyzed ANME-2d sequences, OTU101) grouped with sequences of archaea from sediments of Honghu Lake (HM244209).…”
Section: Diversity Of the Anme-2d 16s Rrna Genes In Librariesmentioning
confidence: 99%
“…In recent years, there has been an active search for microbial agents that carry out AOM in freshwater ecosystems. Recent studies have shown that in oxygen-free soil layers and bottom sediments, anaerobic methanotrophic bacteria, and/or archaea, which are used as electron acceptors of nitrite or nitrate ions, consume methane [19][20][21][22][23][24]. Methane oxidation under anaerobic conditions, which is associated with nitrite reduction, was first demonstrated in the enrichment cultures derived from freshwater sediments [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A). Few aspects about the physiology of ‘ M. nitroreducens ’ are known, and its environmental detection has been limited to molecular methods based on 16S rRNA and mcrA genes (Ding et al ., ). The overview of environmental distribution based on those biomarkers is summarized in Table .…”
Section: The Microbial Ecology and Diversity Of Nitrate‐ And Nitrite‐aommentioning
confidence: 99%
“…As ANME-2d archaea were only recently recognized, their environmental preferences remain insufficiently studied. So far they have been found in freshwater canals [31], soils and rice paddy fields [3436], lakes and rivers [35], and wastewater treatment plants [33]. In situ AOM activity of ANME-2d was determined recently for the first time [36].…”
Section: Introductionmentioning
confidence: 99%